A Review on Pararasasekaram Symptomatology about Karpavippuruthi with Modern Symptomatology (International Journal of Ayurveda and Pharma Research, 2022)
The Siddha System of medicine, which had its presence in the historic Tamil lands one the most of all different clinical structures in the world. Around 4448 illnesses are described through Siddhars of their books and literatures, which might be subdivided into Vatha noi, Pitha noi, Kabha noi, Kasanoi, Soolai, Karapan, Kiraani, Vippuruthi etc. In Vippuruthi noikal Karpavippuruthi is one of the regularly encountered gynaecological illnesses, which turned into cited within the posted literature Pararasasekaram Irandavathu Karparoga Nithanam. The signs and symptoms of Karpavippuruthi cited in the Siddha literature can be correlated with uterine cancer and uterine fibroid in the modern disease of classificatory. The comparative research of Siddha system of medication convey to mild excessive stage of clinical expertise the Siddhars had. The research was focused at evolve a set of absolute Siddha diagnostic strategies for Karpavippuruthi and to correlate the signs and symptoms of Karpavippuruthi with that of carefully akin to situation in modern medical literature. By pertaining to the historic Siddha literature with current day, there could be each augmentation of the expertise of diagnosis and its remedy. This chapter was aimed in delving extensive into the clinical features cited under highly occurring disease “Karpavippuruthi” through Sage Pararasasekaram which in addition ends in shape the Siddha diagnosis and prognostic device of Karpavippuruthi.